Growth and non-structural carbohydrates response patterns of Eucommia ulmoides under salt and drought stress - Zhang, Xuejie; Qin, Hao; Kan, Zhenchao; Liu, Dan; Wang, Bingxin; Fan, Shoujin; Jiang, Peipei (Frontiers in Plant Science, 2024)
Salinity and droughts are severe abiotic stress factors that limit plant growth and development. However, the differences and similarities of non-structural carbohydrates (NSCs) responses patterns of trees under the two stress conditions remain unclear. Here, we determined and compared the growth, physiology, and NSCs response patterns and tested the relationships between growth and NSCs concentrations (or pool size) of Eucommia ulmoides seedlings planted in field under drought and salt stress with different intensities and durations. We found that drought and salt stress can inhibit the growth of E. ulmoides, and E. ulmoides tended to enhance its stress resistance by increasing proline concentration and leaf thickness or density but decreasing investment in belowground biomass in short-term stress. During short-term drought and salt stress, the aboveground organs showed different NSCs response characteristics, while belowground organs showed similar change characteristics: the starch (ST) and NSCs concentrations in the coarse roots decreased, while the ST and soluble sugar (SS) concentrations in the fine roots increased to enhance stress resistance and maintain water absorption function. As salt and drought stress prolonged, the belowground organs represented different NSCs response patterns: the concentrations of ST and SS in fine roots decreased as salt stress prolonged; while ST in fine roots could still be converted into SS to maintain water absorption as drought prolonged, resulting in an increase of SS and a decrease of ST. Significant positive relationships were found between growth and the SS and total NSCs concentrations in leaves and branches, however, no significant correlations were found between growth and below-ground organs. Moreover, relationships between growth and NSCs pool size across organs could be contrast. Our results provide important insights into the mechanisms of carbon balance and carbon starvation and the relationship between tree growth and carbon storage under stress, which were of great significance in guiding for the management of artificial forest ecosystem under the context of global change.